Effect of Music Therapy in Improving Non-verbal Communication Ability in Autism Children - Intan K Dewi; Setyowati BU; I Made Widagda; Dwi Pudjonarko (Indonesian Journal of Physical Medicine & Rehabilitation, 2012)
Objectives: To observe the effect of music therapy in non-verbal communication ability of autism children.Methods : Study design was pre and post test design. Nineteen subjects - 9 was mild-moderate autism (1 girl and 8 boys ) and 10 was severe autism (2 girls and 8 boys), age was between 3-15 years- were applied music therapy by listening 3 children songs from tape recorder,for 15 minutes daily. Childhood Autism Rating Scale (CARS) was conducted to assess severity of autism (mild, moderate, severe) and Early Social Communication Scale (ESCS) to assess ability of non verbal communication with IJA (Initial Joint Attention) and Responding to Joint Attention (RJA). Descriptive statistic and homogeneity test was performed to evaluate the change on CARS and ESCS score in pre and post music therapy p<0.05Results: There was no change on the severity of autism in pre and post test music therapy with 45,394 ± 11.318 become 46.763 ± 10.915 ( p=1.000). There was a significant difference on Early Social Communication Scale (ESCS) pre and post music therapy in group with mild-moderate autism from 2.194 ± 0.496 became 3.833 ± 1.000 ( p = 0.007 ).Conclusions: Music therapy is a supporting therapy that can be given for autism child with mild to moderate autism to improve the ability of non-verbal communicationKeywords: Autism, Music Therapy, Ability of non-verbal communication